2019
DOI: 10.3389/fpsyg.2018.02656
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Counting Skills Between Chinese and German Children Are Accompanied by Differences in Processing of Approximate Numerical Magnitude Information

Abstract: Human beings are supposed to possess an approximate number system (ANS) dedicated to extracting and representing approximate numerical magnitude information as well as an object tracking system (OTS) for the rapid and accurate enumeration of small sets. It is assumed that the OTS and the ANS independently contribute to the acquisition of more elaborate numerical concepts. Chinese children have been shown to exhibit more elaborate numerical concepts than their non-Chinese peers, but it is still an open question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“…For now, due to a lack of evidence, the prediction regarding some symbolic abilities (i.e., verbal number comparisons, the elaboration of number sequences, and approximate addition) remains an open question. In terms of nonsymbolic abilities, we could expect, based on previous studies [5,6], that Vietnamese children may have a slightly better ANS acuity than Belgian children. Furthermore, based on previous studies [36,38], we assumed that cross-cultural differences in home numeracy would also contribute to the differences between the two samples in the numerical tasks.…”
Section: Present Studymentioning
confidence: 94%
See 4 more Smart Citations
“…For now, due to a lack of evidence, the prediction regarding some symbolic abilities (i.e., verbal number comparisons, the elaboration of number sequences, and approximate addition) remains an open question. In terms of nonsymbolic abilities, we could expect, based on previous studies [5,6], that Vietnamese children may have a slightly better ANS acuity than Belgian children. Furthermore, based on previous studies [36,38], we assumed that cross-cultural differences in home numeracy would also contribute to the differences between the two samples in the numerical tasks.…”
Section: Present Studymentioning
confidence: 94%
“…Based on these results, some authors have hypothesized that a transparent number-naming system (e.g., "ten-one" for 11), which may enhance Chinese children's learning of symbolic numbers [29], could also boost children's processing of non-symbolic numbers [5,6,30]. Accordingly, previous studies have showed that Chinese children (5-to 7-year-olds and 4-to 6-year-olds) tend to perform moderately better on a non-symbolic numerical task than British and German children, respectively [5,6]. Similarly, Dowker and Roberts [30] demonstrated that Welsh children (in grade 2) who speak a language with the same number-word structure transparency as Asian languages performed better on non-verbal line estimations than their English peers.…”
Section: Effect Of Language On the Numerical Development Of Preschoolersmentioning
confidence: 99%
See 3 more Smart Citations